Establishing Role of Cheiloscopy in Person Identification and Sex Determination - Kesarwani, Pallavi; Choudhary, Anand (Journal of Orofacial Research, 2017)
Background: The study of lip prints (LP) is known as Cheiloscopy. Every individual has a unique lip print pattern. Thus it can act as an important tool for person identification in civil and criminal cases. Objective: The aim of this study is to ascertain whether the uniqueness of LP can help in identifying a person, to evaluate the varied lip patterns among males and females and its usefulness in gender discrimination. Materials and methods: A cross-sectional study was conducted on 80 undergraduate students (40 males and 40 females) of Hazaribagh Dental College aged between 18 to 24years. The lipstick was applied evenly on both the lips and then the LP was collected. Later these lip patterns were analyzed and interpreted. Results: 35 out of 40 LP of females and 36 out of 40 LP of males were correctly matched. Type I and I’ were predominantly seen in females while type IV and V patterns were more common among males. A total of 73 of 80 subjects were identified correctly by this method. Conclusion: The result suggests that the uniqueness of LP in forensic dentistry can be explored for law implementation by determining gender and person’s identity.